PERAN PENYULUH TERHADAP IMPLEMENTASI PENGELOLAAN OPT DALAM RANGKA KEBERLANJUTAN EKOSISTEM PERTANIAN SERTA KAITANNYA DENGAN PRODUKTIVITAS PADI SAWAH DI KABUPATEN ASAHAN - Eryanto, Oktoni; Kuswardani, Retno Astuti; Noer, Zulheri; Aulia, Muhammad Reza (Agros Journal of Agriculture Science, 2023)
A study of the role of extension workers in the implementation of OPT management in the context of sustainable agricultural ecosystems and its relation to lowland rice productivity in Asahan Regency is very relevant to carry out. Analyzing the impact of the role of extension workers on the use of different pest management techniques in encouraging the adoption of sustainable practices will provide valuable insights for the development of more sustainable agriculture, reducing environmental and health risks, and increasing farmer productivity and welfare. The research method used is "Field Research" with a "Case Study" approach. The research results show that lowland rice farmers in Asahan Regency have implemented various components of sustainable management of Plant Pest Organisms (OPT) using various approaches. They use physical, mechanical, technical culture, resistant varieties, biological control techniques, as well as control with rules and regulations to face the challenges of plant pests and diseases. Through a combination of these techniques, farmers strive to achieve a balance between the effectiveness of pest control and their positive impact on the environment Keywords: extension agent, OPT, sustainability INTISARIKajian tentang peran penyuluh terhadap implementasi pengelolaan OPT dalam rangka keberlanjutan ekosistem pertanian serta kaitannya dengan produktivitas padi sawah di Kabupaten Asahan sangat relevan untuk dilakukan. Dengan menganalisis dampak dari peran penyuluh terhadap penggunaan teknik pengelolaan OPT yang berbeda dalam mendorong adopsi praktek-praktek berkelanjutan, akan memberikan wawasan berharga bagi pengembangan pertanian yang lebih berkelanjutan, mengurangi risiko lingkungan dan kesehatan, serta meningkatkan produktivitas dan kesejahteraan petani. Metode penelitian yang digunakan adalah “Penelitian Lapangan” dengan pendekatan “Studi Kasus.” Hasil penelitian menunjukkan bahwa petani padi sawah di Kabupaten Asahan telah mengimplementasikan berbagai komponen pengelolaan Organisme Pengganggu Tanaman (OPT) berkelanjutan dengan beragam pendekatan. Mereka menggunakan teknik pengendalian fisik, mekanik, kultur teknis, varietas tahan, hayati, serta pengendalian dengan peraturan dan regulasi untuk menghadapi tantangan hama dan penyakit tanaman. Melalui kombinasi teknik ini, petani berupaya mencapai keseimbangan antara efektivitas pengendalian hama dan dampak positifnya bagi lingkungan Kata kunci: penyuluh, OPT, keberlanjutan